2017
DOI: 10.1016/j.wep.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Different preferences for wine communication

Abstract: This study aimed at verifying the presence of variations in the reactions of different types of audiences to certain communication tools for wine. Five samples of audiences were compared: wine professionals, organic produce specialists, wine tourists, and two samples of general tourists. The following bundle of attributes were considered: name of the grape; information on organic production methods; type of closure; QR code; landscape; advertising language. Diverse audience's preferences were measured by conjo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…An e-commerce company specializing in the distribution of wine also assisted in forwarding the survey to clientele. In keeping with recent calls for studies that provide insight into cognitive consumer processes prior to purchase (Lockshin et al, 2017;Nunes et al, 2016;Sillani et al, 2017), the research was conducted offpremise, as such respondents were not asked to select from a collection of wine but rather they evaluated the attributes in absence of the physical product. No particular parameters were set for the consumption process or occasion of consumption, with the context of the questions relating specifically to the individual respondent's knowledge of wine, based on the questions posed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An e-commerce company specializing in the distribution of wine also assisted in forwarding the survey to clientele. In keeping with recent calls for studies that provide insight into cognitive consumer processes prior to purchase (Lockshin et al, 2017;Nunes et al, 2016;Sillani et al, 2017), the research was conducted offpremise, as such respondents were not asked to select from a collection of wine but rather they evaluated the attributes in absence of the physical product. No particular parameters were set for the consumption process or occasion of consumption, with the context of the questions relating specifically to the individual respondent's knowledge of wine, based on the questions posed.…”
Section: Methodsmentioning
confidence: 99%
“…Presented with a limited set of attributes, the expressed preference would thus be more easily differentiated in terms of its relative importance. Furthermore, the study did not include visual representations, labeling or packaging as attributes, as literature has proposed that consumer perception is heavily influenced by other referent and cultural factors (Sillani, Miccoli, & Nassivera, 2017), which in essence don't form part of the scope of this study. Although research assessing the relative importance of these respective attributes in various market segments is in existence, no work has served to examine the extent to which these extrinsic cues configure across the various self-assessed and objectively measured product knowledge typologies.…”
Section: Product Attributesmentioning
confidence: 99%
“…[...] Results showed that information level had a significant effect on all investigated variables [...] and a substantial increase in willingness to pay" [21]. Sillani et al [22] also studied "the presence of variations in the reactions of different types of audiences to certain communication tools for wine".…”
Section: Storytelling Literature In Food and Winementioning
confidence: 99%
“…From the conjoint analysis, the researchers discovered that "textual language was more effective with professionals, while the photographic language was more effective with tourists. Supplementary information on the organic production methods, in addition to the mandatory labelling requirements, increased the preferences of professionals and wine tourists and was counterproductive with the general customers [22]. Besides, Malorgio et al in 2008 [23] state that, for Italian consumers, "the use of the designation of origin to assess quality at the moment of purchase requires a certain level of product knowledge and involvement" while the individual brand is described as a helpful tool to identify the wine and to link it to past consumption experiences.…”
Section: Storytelling Literature In Food and Winementioning
confidence: 99%
“…Conjoint analysis was used to evaluate consumer preference towards bread by decomposing total preference in partial preferences relevant to independent product attributes (De Pelsmaeker et al, 2017;Sillani et al, 2017). Five attributes of bread containing lettuce flour were selected as experimental variables and named 'lettuce flour', 'health', 'waste recovery', 'waste reduction' (discrete variables) and 'price' (linear variable).…”
Section: Consumer Responsementioning
confidence: 99%